Invasion by Toxoplasma gondii establishes a moving junction that selectively excludes host cell plasma membrane proteins on the basis of their membrane anchoring. - Mordue, D; Desai, N; Dustin, M; Sibley, L (1999)
The protozoan parasite Toxoplasma gondii actively penetrates its host cell by squeezing through a moving junction that forms between the host cell plasma membrane and the parasite. During invasion, this junction selectively controls internalization of host cell plasma membrane components into the parasite-containing vacuole. Membrane lipids flowed past the junction, as shown by the presence of the glycosphingolipid G(M1) and the cationic lipid label 1. 1'-dihexadecyl-3-3'-3-3'-tetramethylindocarbocyanine (DiIC(16)). Glycosylphosphatidylinositol (GPI)-anchored surface proteins, such as Sca-1 and CD55, were also readily incorporated into the parasitophorous vacuole (PV). In contrast, host cell transmembrane proteins, including CD44, Na(+)/K(+) ATPase, and beta1-integrin, were excluded from the vacuole. To eliminate potential differences in sorting due to the extracellular domains, parasite invasion was examined in host cells transfected with recombinant forms of intercellular adhesion molecule 1 (ICAM-1, CD54) that differed in their mechanism of membrane anchoring. Wild-type ICAM-1, which contains a transmembrane domain, was excluded from the PV, whereas both GPI-anchored ICAM-1 and a mutant of ICAM-1 missing the cytoplasmic tail (ICAM-1-Cyt(-)) were readily incorporated into the PV membrane. Our results demonstrate that during host cell invasion, Toxoplasma selectively excludes host cell transmembrane proteins at the moving junction by a mechanism that depends on their anchoring in the membrane, thereby creating a nonfusigenic compartment.